2014
DOI: 10.5934/kjhe.2014.23.4.599
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Preschool Children's Gender, Temperament, Emotional Regulation and Maternal Parenting Stress on Children's Overt Aggression and Relational Aggression

Abstract: The purposes of this study were (1) to explore the gender differences in children's overt aggression and relational aggression and (2) to investigate the effects of preschool children's gender, temperament, emotional regulation, and maternal parenting stress on overt aggression and relational aggression. The participants were 173 preschool children and their mothers from three day care center and two kindergarten in Seoul and Gyeong-gi province. The data were analyzed using descriptive statistics, t-test, corr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 29 publications
0
5
0
1
Order By: Relevance
“…In addition, children's ability to properly manage their emotions contributes to help children respond appropriately to the environment and to establish functional social relationships (Denham et al, 2003; Rydell, Berlin, & Bohlin, 2003); in pursuit of personal goals, on the other hand, failure to acquire successful coping strategies with stimulating contexts can contribute to adaptation difficulties characterized as emotional and inadequate behavioral or excessive control and which exacerbate clinical and related externalization or internalization problems (for examination, see Calkins & Hill, 2007; Mullin & Hinshaw, 2007). The studies discussed in this context show that experiencing negative emotions with high levels and also being unsuccessful in emotional regulation is associated with problem behaviors such as externalization (such as aggression, risk-taking, and hyperactivity) and internalization and show that the development of emotional regulation skills plays a crucial role in reducing the problem behavior of these children (Arı & Yaban, 2016; Blandon, Calkins, Grimm, Keane, & O'Brien, 2010; Calkins & Fox, 2002; Calkins, Smith, Gill & Johnson, 1998; Chang, Schwartz, Dodge, & McBride-Chang, 2002; Cicchetti, Ackerman, & Izard, 1995; Hanish et al, 2004; Helmsen et al, 2012; Helmsen, Koglin, & Peterman, 2012; Hill, Degnan, Calkins, & Keane, 2006; Jun Ah, Yoonjoo, & Jihyun, 2014; Miller et al, 2006; Ramsden & Hubbard, 2002; Romanchych, 2014; Rothbart & Bates, 2006; Rubin et al, 1995; Rubin, Coplan, Fox, & Calkins, 1995; Ural, Güven, Sezer, Efe-Azkeskin, & Yılmaz, 2015). These research results show that children with low emotional regulation skills experience behavioral problems in the classroom, and this influences their classroom adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, children's ability to properly manage their emotions contributes to help children respond appropriately to the environment and to establish functional social relationships (Denham et al, 2003; Rydell, Berlin, & Bohlin, 2003); in pursuit of personal goals, on the other hand, failure to acquire successful coping strategies with stimulating contexts can contribute to adaptation difficulties characterized as emotional and inadequate behavioral or excessive control and which exacerbate clinical and related externalization or internalization problems (for examination, see Calkins & Hill, 2007; Mullin & Hinshaw, 2007). The studies discussed in this context show that experiencing negative emotions with high levels and also being unsuccessful in emotional regulation is associated with problem behaviors such as externalization (such as aggression, risk-taking, and hyperactivity) and internalization and show that the development of emotional regulation skills plays a crucial role in reducing the problem behavior of these children (Arı & Yaban, 2016; Blandon, Calkins, Grimm, Keane, & O'Brien, 2010; Calkins & Fox, 2002; Calkins, Smith, Gill & Johnson, 1998; Chang, Schwartz, Dodge, & McBride-Chang, 2002; Cicchetti, Ackerman, & Izard, 1995; Hanish et al, 2004; Helmsen et al, 2012; Helmsen, Koglin, & Peterman, 2012; Hill, Degnan, Calkins, & Keane, 2006; Jun Ah, Yoonjoo, & Jihyun, 2014; Miller et al, 2006; Ramsden & Hubbard, 2002; Romanchych, 2014; Rothbart & Bates, 2006; Rubin et al, 1995; Rubin, Coplan, Fox, & Calkins, 1995; Ural, Güven, Sezer, Efe-Azkeskin, & Yılmaz, 2015). These research results show that children with low emotional regulation skills experience behavioral problems in the classroom, and this influences their classroom adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…It is known that children who cannot deal constructively with their anger show more externalizing symptoms (Zeman et al, 2002) and that children who have difficulty dealing with their negative emotions use ineffective strategies to resolve their emotional and behavioral problems (Jones et al, 2002; Rogers et al, 2016). However, many studies have shown that the development of emotional regulation skills in preschool children plays an important role in reducing their aggression (Blandon et al, 2010; Chang et al, 2003; Hanish et al, 2004; Helmsen et al, 2012; Jun Ah et al, 2014; Miller et al, 2006; Ramsden & Hubbard, 2002; Roberton et al, 2012; Röll et al, 2012; Romanchych, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Emotionally vulnerable young children are easily irritated and can sometimes perceive well‐intended actions as aggression and respond to such actions with aggressive behavior of their own (Goleman, 2018). Much research (Arı & Yaban, 2016; Blandon et al, 2010; Chang et al, 2003; Hanish et al, 2004; Helmsen et al, 2012; Jun Ah et al, 2014; Miller et al, 2006; Ramsden & Hubbard, 2002; Romanchych, 2014; Ural et al, 2015) has found that the development of emotional regulation skills in preschool children plays an important role in reducing aggressive behavior. Moreover, it has been found that the development of emotional regulating skills is important because it enables preschool children to manage their emotions appropriately, and it plays a crucial role in reducing and preventing aggression (August et al, 2017; Landy & Menna, 2001).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Okul öncesi dönem çocuklarının duygu düzenleme becerilerinin gelişiminin, bu çocukların fiziksel saldırganlık düzeylerini azaltmada çok önemli bir rol oynadığını ortaya koyan pek çok çalışma (Arı ve Yaban, 2016;Blandon, Calkins, Grimm, Keane ve O'Brien, 2010;Calkins, Smith, Gill ve Johnson, 1998;Chang vd., 2002;Cicchetti, Ackerman ve Izard, 1995;Hanish vd., 2004;Helmsen, Koglin ve Peterman, 2012;Romanchych, 2014;Rubin, Coplan, Fox ve Calkins, 1995;Ural vd., 2015) bulunmaktadır. Bununla birlikte duygu düzenleme becerilerinin gelişiminin çocukların ilişkisel saldırganlıkları ile ilişkisi sınırlı sayıda çalışmada (Arı ve Yaban, 2016;Ostrov vd., 2013;Jun Ah, Yoonjoo ve Jihyun, 2014;Mihic, Novak, Basic ve Nix, 2016) ele alınmıştır. Oysa yapılan çeşitli araştırmalarda (Ostrov, Ries, Stauffacher, Godleski ve Mullins, 2008;Murray Close ve Ostrov, 2009) çocuklarda gözlenen ilişkisel saldırganlık ile fiziksel saldırganlık arasında yüksek düzeyde ve pozitif yönde ilişkili bulunmuştur.…”
Section: Introductionunclassified